Implementasi Metode Fuzzy - AHP Menggunakan Optimasi Particle Swarm Optimization (PSO) untuk Rekomendasi Pemilihan Tanaman Pomologi - Maulana Putra Pambudi; Imam Cholissodin; Candra Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Pomology (fruit) is one of the most popular commodities in Indonesia. But, in indonesia fruit production rate is not bigger than fruit consumption rate. Lack of fruit production in Indonesia can be caused by various factor. One of the factor is production failure that caused by wrong fruit choice. That factor can happen because lack of farmer knowledge about compatibility between land and fruit. Therefore it takes a program that can used to help farmer check if their land is compatible with one kind of fruit or not. FAHP-PSO is a one of the method that can solve a problem with many determining factor inside it. This method is a combination of 2 previous method. That 2 previous method is Fuzzy-AHP and Particle Swarm Optimization (PSO). Particle Swarm Optimization method will be working to optimize criteria weight ratio that should be generated from AHP. From the test result, Spearman coefficient for comparing rank result in 3 land and 10 fruit is 0.8598. beside that from the classification result we can obtained Spearman coefficient is 0.9659.